Plant biostimulant on the production of biomass and yield grain of soybean / Bioestimulante vegetal e períodos de corte na produção de biomassa e rendimentos de grãos de soja - Jeandson Silva Viana; João Paulo Ramos de Melo; Júlio César de Almeida Silva; Edilma Pereira Gonçalves; Juliana Joice Pereira Lima; Wallace Rodrigues Telino Júnior; Jeandson Silva Viana (Universidade Estadual de Alagoas, 2019)
With the growing interest in the search for food resources that may partially replace the use of concentrates in animal feed, the cultivation of soybeans for the production of biomass and grains responds as an alternative to the livestock sector. Therefore, the objective of this research was to test doses of phytostimulant and cut-off periods to evaluate the phytomass gain and soybean grains yield in the Agreste Meridional region of the state of Pernambuco, Brazil. The experiment was carried out under field conditions, in the city of Garanhuns, evaluating four doses of phytostimulant (F1=0.00, F2 = 3.75, F3 = 7.50 and F4 = 11.25 mL kg-1 of seeds) and four cut-off periods (C1= no cut; C2 = 30 DAE (days after sowing); C3 = 35 DAE and C4 = 40 DAE). The dry mass of the plants was increased when cutting was done later, the increment in this period was verified with the application of the higher doses of phytostimulant, contributing to the elevation in height, number of nodes and green biomass. The phytostimulant dose of 7.5 mL kg-1 of seed and the cut-off period of 40 days after emergence (DAE) are the most indicated for forage, for providing greater biomass gain. Cutting at 30 DAE associated with the phytostimulant dose of 4.36 mL kg-1 of seeds provided a higher production of regrowth grains.